Manajemen Risiko dalam Upaya Resiko Muzakki dan Mustahiq pada lembaga MPZ Citra Anak Sholeh - Achmad Ali Mustofa (Jurnal Ilmiah Ekonomi Islam, 2022)
At this time the population in the city of Surabaya is around 2.8 million people, the data comes from the Central Statistics Agency for the province of East Java. From these data, it becomes an opportunity for philanthropic institutions in the city of Surabaya. The fraud above is an obstacle to raising the reputation of the Amil zakat institution in Indonesia. The case above has added to the urgency in risk management that must be carried out by all BAZ and LAZ institutions so that this does not happen again. In this study, ERM Enterprise Risk Management was used through the COSO Committee Of Sponsoring of the treadway commission approach. The results of the risk assessment of muzakki and mustahiq MPZ Citra Anak Sholeh show that there are 11 risks that are indicated as low risk and eight risks that are moderate or in the medium stage. Risk data with a high opportunity and impact measure are muzakki who donate their zakat to more than one amil zakat institution. Risk Handling Muzakki and mustahiq MPZ Citra Anak Sholeh held a sharing discussion internally and externally with LAZ Yatim Mandiri. MPZ Citra Anak Sholeh identifies the problem, then makes anticipation regarding the risks that will occur. muzakki who donate their zakat to more than one amil zakat institution. According to the leadership of the MPZ institution, it is necessary to identify the reasons why the muzakki donated to the two institutions, so that it is known specifically what strategy will be made to attract the muzakki.